Knowledge, Use, and Perception of Brazilian Women about Contraceptive Methods: An Observational Study - Juliana Dineia Perez Brand?o; Rogerio Bonassi Machado; Ana Carolina Ferreira Cardoso (Mary Ann Liebert, 2024)
Background: In Brazil, where approximately 48.7 million women are of reproductive age, understanding contraceptive practices is essential for addressing public health challenges. This study evaluated into the knowledge, usage, and perceptions of contraceptive methods among Brazilian women, highlighting the influence of socioeconomic and demographic factors on their choices. Methods: We conducted a cross-sectional survey with a representative sample of 2000 Brazilian women aged 18?49 years. The questionnaire collected detailed information on their awareness, preferences, and utilization of various contraceptive methods, alongside demographic and socioeconomic data. Results: Oral contraceptives, condoms, injectables, and intrauterine devices (IUDs) were the most recognized methods. Younger women demonstrated greater awareness of modern methods. Socioeconomic disparities were evident, with lower-income women displaying limited knowledge about condoms and IUDs but a higher usage for injectable contraceptives. Oral contraceptives were the most used method, with higher use in the South, and lower in the Central-West and Northeast regions. Satisfaction with current contraceptive methods was high (87.5%), closely associated with personal responsibility in method choice. Although the majority self-financed their contraceptives (63.1%), a significant portion of lower-income women (27.7%) relied on public health care. Physicians? recommendations predominantly influenced contraceptive choice (53.9%), with younger women also guided by other influences. Conclusions: Persistent disparities in contraceptive awareness and access highlight the need for educational initiatives and policy interventions. Health care providers play a vital role in facilitating informed contraceptive choices, enhancing the chances of satisfaction with the method.